Exploring the Impact of Social, Cultural, and Science Factors on Students’ STEM Career Preferences - Nasser Mansour (17541822) (2024)
The declining interest in STEM careers in the United Kingdom has raised concerns, prompting this study to explore the intricate relationship between social, cultural, and scientific identities and their impact on students’ inclination towards science and technology career pathways. Additionally, the study examines the associations between gender, gender-related job preferences, and career choices. Data were collected from 1,618 primary and secondary students in the UK. Descriptive and inferential statistics, including regression analysis and multivariate analysis, were employed for analysis. The key findings revealed a significant interaction effect between gender and gender-related job preferences. Social factors were identified as significant mediators, amplifying the influence of gender on career decisions and shaping gender-related job preferences. Cultural factors, particularly related to ethnicity, were found to shape job preferences, while religious affiliation did not exhibit a significant effect. Students’ perceptions of science, stereotypes associated with science professionals, and engagement in science extracurricular activities were positively correlated with a greater likelihood of expressing interest in STEM careers, demonstrating the influential impact of science factors on forming students’ STEM career choices. Interestingly, the type of education (primary or secondary) did not significantly impact job preferences, suggesting that preferences may become more refined or influenced by external factors as students progress in their education. Other Information Published in: Research in Science Education License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11165-024-10210-4